Analysis of demand and access to services in the last two weeks previous to the National Health Survey 2013 and 2019 - Deborah Carvalho Malta; Crizian Saar Gomes; Elton Junio Sady Prates; Fausto Pereira dos Santos; Wanessa da Silva de Almeida; Sheila Rizzato Stopa; Cimar Azeredo Pereira; Célia Landmann Szwarcwald
ABSTRACT Objective Compare the demand and use of health services between 2013 and 2019, and analyze the associated sociodemographic and health variables in 2019. Methods: Cross-sectional study with data from the National Health Survey (PNS) 2013 and 2019. The prevalence and 95% confidence intervals (95% CI) for the demand and use of health services were estimated. In 2019, the differences in the indicators were analyzed according to sociodemographic variables and the crude and adjusted by sex and age prevalence ratios (RP) were estimated. Results: There was an increase of 22% in the demand for health care in the last two weeks, going from 15.3% (95%CI 15.0-15.7) in 2013 to 18.6% (95%CI 18.3-19.0) in 2019. There was a reduction in use in the last two weeks, from 97% (95%CI 96.6-97.4) in 2013 to 86.1% (95%CI 85.4-86.8) in 2019, which was observed for most Federation Units. In 2019, the demand for care was greater among women, the elderly, those with high schooling, individuals with health insurance and poor self-rated health. They obtained greater access to health services in the fifteen days prior to the survey: men, children or adolescents up to 17 years of age, people with health insurance and poor health self-assessment. Conclusion: The demand for health services has grown and reduced access in the last 15 days between 2013 and 2019. These differences may have been exacerbated by the austerity measures implemented in the country.